ТHE FEATURES OF VERBAL COMMUNICATIONS IN PUBLICGOVERNANCE IN THE CONDITIONS OF ADMINISTRATIVE REFORM - TELETOV, ALEXANDR; TELETOVА SVETLANA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article considers verbal communications in public administration of united territorial communities in order to make their functioning more effective. It is shown that in the minds of the administrative reform and the increasing the local self-government advancement role of the verbal communication on the basis of the information exchanged, direct to the management of the publication functions. It is confirmed that marketing techniques and tools are increasingly used by managers of non-manufacturing firms and companies, because they give government and municipal officials certain benefits in creating conditions for sustainable development and improving the quality of life, which is especially important during administrative reform, organization of united territorial communities, amalgamation of districts. It is believed that in the context of decentralization of territorial management tools of verbal communication, information exchange, presentation and legitimation of public administration will provide targeted management influence on potential consumers and the general public. It is shown that in order to support their actions on the part of society, managers and marketers have their own advertisements for goods and services, texts of TV and radio messages, posters and billboards, communicative public relations models, Internet advertising and others to combine as much as possible with goods and services of opposite value categories (social orientation), which are demonstrated with the communication use of certain verbal means. Thus, it is proved that the use of marketing communication approaches and tools in the public administration system, fixing them in relevant regulations and use the specialists of state and local governments at all levels in their activities is not only appropriate but necessary.